MEDIA PEMBELAJARAN KARTU PERKALIAN BERBASIS PERMAINAN MONOPOLI UNTUK MENINGKATKAN KEMAMPUAN PERKALIAN SISWA KELAS III SEKOLAH DASAR - Wayan Eka Muliawan, I; Gusti Ayu Tri Agustiana, I; Made Hendra Sukmayasa, I (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low multiplication skills of third-grade elementary school students, in which 73% of students did not achieve the Minimum Mastery Criteria (MMC). The problem was caused by teacher-centered learning and the limited use of game-based learning media. This study aimed to develop a multiplication card learning media based on the Monopoly game and to determine its validity, practicality, and effectiveness. This research employed the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The results showed that the developed media was categorized as highly valid and highly practical, and it was effective in improving students’ multiplication skills. Therefore, the Monopoly-based multiplication card media is feasible to be used as an innovative alternative in third-grade mathematics learning.